2014
DOI: 10.1093/pch/19.7.e113
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparity and perception of obesity/overweight by parents and grandparents

Abstract: Misconceptions about a child's weight status were prevalent among parents and grandparents, and boys' weight status was more frequently underestimated than girls. The disparity of underestimating weight according to sex may partially contribute to the difference in the prevalence of obesity/overweight between boys and girls among Chinese school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…Parents of overweight/obese children reported less daily activity time and more time spent watching television. In addition, similar to other studies, we found that parents often underestimated their child’s weight, especially when children were overweight or obese [11, 21, 27, 30, 33], and that there were gender differences in parental perception of child weight, with a tendency for parents to underestimate weight more in boys than in girls [17, 20, 21, 33]. Interestingly, we found a larger difference between parent perception of child’s weight and measured weight status in obese children than in overweight children.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Parents of overweight/obese children reported less daily activity time and more time spent watching television. In addition, similar to other studies, we found that parents often underestimated their child’s weight, especially when children were overweight or obese [11, 21, 27, 30, 33], and that there were gender differences in parental perception of child weight, with a tendency for parents to underestimate weight more in boys than in girls [17, 20, 21, 33]. Interestingly, we found a larger difference between parent perception of child’s weight and measured weight status in obese children than in overweight children.…”
Section: Discussionsupporting
confidence: 89%
“…Parents often incorrectly categorize children as normal weight even when they are considered overweight/obese based on measured BMI [11, 15, 21, 27, 30, 33]. Such misperceptions are more common for younger children and boys, by an overweight or obese parent, and in families that are of minority race/ethnicity and lower socioeconomic status [8, 1113, 17, 2022, 30, 33]. Literature is limited regarding how overall perception of a child’s health or reported lifestyle behaviors relate to perception of weight.…”
Section: Introductionmentioning
confidence: 99%
“…30 -32 In this study, the progression to overweight or obese BMI among girls appeared to be less sensitive to the intervention measures, a finding which is somewhat consistent with other studies. [32][33][34] It is possible that sociocultural factors account for these observed sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Older people in China viewed being overweight as a sign of good health in children rather than as a negative condition (11). In Indonesia, it is not entirely understood why parents tend to have overweight children.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies have focused on the factors associated with parental misperception. It has been reported that children's weight is more likely to be estimated incorrectly by their parents when the child is more overweight (8)(9)(10), male (9,11,12), or older (8,13). Furthermore, mothers with low levels of education or low body mass index (BMI) were found to have a poor ability to classify their children's weight status, correctly (10,14).…”
Section: Introductionmentioning
confidence: 99%